2019
DOI: 10.3390/nu12010013
|View full text |Cite
|
Sign up to set email alerts
|

Decursin and Decursinol Angelate Suppress Adipogenesis through Activation of β-catenin Signaling Pathway in Human Visceral Adipose-Derived Stem Cells

Abstract: Visceral adiposity is closely associated with metabolic disorders and cardiovascular diseases. Angelica gigas Nakai (AGN) has been reported to possess anti-obesity effects and higher amounts of coumarin compounds are present in AGN. However, the active compounds suppressing adipogenesis in AGN and mechanisms of action have not been investigated in adipose-derived stem cells (ASCs) isolated from visceral adipose tissue (VAT). Among four coumarin compounds of AGN, decursin (D) and decursinol angelate (DA) signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Therefore, the anti-adipogenic effect of Res and Pic in vASCs may regulate the SIRT1, AMPK, and AKT signaling pathways, and the expression levels of SIRT1, AMPK, and AKT may show different levels between Res and Pic treatment. Increasing evidence suggests that nutraceuticals from natural products attenuate adipogenesis in mesenchymal stem cells by activating the wingless-type mouse mammary tumor virus (MMTV) integration site (WNT)/β-catenin signaling pathways [ 37 , 38 ]. Therefore, it would be interesting to study the underlying molecular mechanisms involved in regulating the adipogenesis of vASCs by Res and Pic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the anti-adipogenic effect of Res and Pic in vASCs may regulate the SIRT1, AMPK, and AKT signaling pathways, and the expression levels of SIRT1, AMPK, and AKT may show different levels between Res and Pic treatment. Increasing evidence suggests that nutraceuticals from natural products attenuate adipogenesis in mesenchymal stem cells by activating the wingless-type mouse mammary tumor virus (MMTV) integration site (WNT)/β-catenin signaling pathways [ 37 , 38 ]. Therefore, it would be interesting to study the underlying molecular mechanisms involved in regulating the adipogenesis of vASCs by Res and Pic.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mice were fed HFD to induce weight gain through an increase in energy intake. BJT has long been used to treat edema and dampness-phlegm [11], and its components have been shown to have antiobesity activities [12][13][14][15][16][17][18][19][20], but the pharmacological activity of BJT has not yet been investigated. In the present study, we found that BJT suppressed HFDinduced weight gain in an obese mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The compound MDG-1 from Ophiopogon japonicas shows potent hypoglycemic and weight control effects in mice [17]. Decursin, present in Angelica gigas Nakai, has an antiadipogenic effect in adipose-derived stem cells isolated from human visceral adipose tissue [18]. Akebia quinata extract also has antiobesity and hypolipidemic effects in HFD-fed mice [19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the biological activities of decursin have been revealed widely. 18 Decursin has antioxidative and anti-inflammation effects in several diseases. 19 Decursin inhibits osteoclast formation and bone loss both in vitro and in vivo.…”
Section: Decursin Relieves Oxidative Stress In Beas-2b and Hpaec Cell...mentioning
confidence: 99%